Modified mRNA as an alternative to plasmid DNA (pDNA) for transcript replacement and vaccination therapy. (September 2015) - Youn, Hyewon; Chung, June-Key
<x xml:space="preserve">Abstract</x> Introduction: Current gene therapy involves replacement of defective gene by delivery of healthy genetic material to precede normal function. Virus-mediated gene delivery is the most successful and efficient method for gene therapy, but it has been challenged due to serious safety concerns. Conversely, gene delivery using plasmid DNA (pDNA) is considered safer, but its transfection efficiency is much lower than virus-mediated gene transfer. Recently, mRNA has been suggested as an alternative option to avoid undesired insertion of delivered DNA sequences with higher transfection efficiency and stability. Area covered: In this review, we summarize the currently available strategies of mRNA modification to increase the therapeutic efficacy; we also highlight the recent improvements of mRNA delivery for in vivo applications of gene therapy. Expert opinion: The use of mRNA-based gene transfer could indeed be a promising new strategy for gene therapy. Notable advantages include no risk of integration into the genomic DNA, adjustable gene expression and easier modulation of the immune system. By reducing or utilizing the immunogenic properties, mRNA offers a promising tool for gene/or transcript replacement.